PENGEMBANGAN PENDIDIKAN PESANTREN DALAM MENINGKATKAN PROFESIONALISME SANTRI (STUDI PADA PONDOK PESANTREN SALAFIYAH SYAFI’IYAH NURUL HUDA MERGOSONO MALANG) - Iqbal Maulana Ismail; Mazda Husniyah (Transformatif, 2020)
The development of science that is so fast result in changing human religion, either in the economic, social, political, technological or educational realms. Therefore, boarding school which is an Islamic educational institution must be aware of the existence of this phenomenon by making improvements on the human resources order, which is supported by the application of good and effective human resource management patterns so that later boarding school graduates are not only considered to have mastered religious knowledge but also to compete outside the Islamic realm. This research aims to explain, that boarding schools as an Islamic educational institution that has long been present in the archipelago, is able to compete with other formal educational institutions. That is by continuing to try to modernize the pattern of education and integrate with various activities that practice the ability of students, so that they can become students who have expertise not only in the religious field, but also in the non-religious realm. This research uses a qualitative method with a descriptive analysis approach. Data obtained by conducting interviews and direct observations at the Salafiyah Syafi’iyah Nurul Huda Islamic Boarding School, While the data analysis technique uses a hermeneutics approach that uses a thorough understanding and interpretation. The results of this research show that the Salafiyah Syafi'iyah Islamic Boarding School Nurul Huda has attempted to develop the professionalism of students by coordinate their education systems to meet the needs and demands of the times. This can be seen by the existence of programs outside the core learning in boarding school. Among them in the form of Graphic Design, Screen Printing Clothes and Scientific Work.